Recombinant Bivalent Live Vectored Vaccine Against Classical Swine Fever and HP-PRRS Revealed Adequate Heterogeneous Protection Against NADC30-Like Strain - Li, Liwei; Chen, Jinxia; Cao, Zhengda; Cao, Yunlei; Guo, Ziqiang; Tong, Wu; Zhou, Yanjun; Li, Guoxin; Jiang, Yifeng; Liu, Changlong; Yu, Lingxue; Qiao, Sina; et al. (Frontiers in Microbiology, 2022)
The recombinant bivalent live vectored vaccine rPRRSV-E2 has been proved to be a favorable genetic engineering vaccine against classical swine fever (CSF) and highly-pathogenic porcine reproductive and respiratory syndrome (HP-PRRS). NADC30-like strains have recently emerged in China and caused severe disease, and it is necessary to evaluate the vaccine candidate for the currently circulating viruses. This study established a good challenge model to evaluate the candidate rPRRSV-E2 vaccine in preventing infection with a representative NADC30-like strain (ZJqz21). It was shown that the challenge control piglets displayed clinical signs typical of PRRSV, including a persistent fever, dyspnea, moderate interstitial pneumonia, lymph node congestion, and viremia. In contrast, the rPRRSV-E2 vaccination significantly alleviated the clinical signs, yielded a high level of antibodies, provided adequate protection against challenge with ZJqz21, and inhibited viral shedding and the viral load in target tissues. Our results demonstrated that the recombinant bivalent live vectored vaccine strain rPRRSV-E2 can provide efficient protection against the challenge of heterologous circulating NADC30-like strain and could be a promising vaccine candidate for the swine industry.